اتجاهات التغير في سلاسل الهطولات السنوية والفصلية في بعض مواقع المنطقة الساحلية في سورية - شيخو, طاهر (Latakia University Journal -Biological Sciences Series, 2014)
تم في هذه الدراسة تقدير التغير في الكميات السنوية والفصلية للهطل للفترة (2006-1971) في ثلاث محطات ميتيورولوجية (اللاذقية، طرطوس وصافيتا) تقع في المنطقة الساحلية من سورية، باستخدام اختباري الانحدار الخطي ومعامل سبيرمان لارتباط الرتب. أظهرت النتائج اتجاهاً نحو تناقص المعدلات السنوية للهطل في محطتي اللاذقية وطرطوس، ونحو تزايدها في محطة صافيتا. وعلى المستوى الفصلي، لوحظ اتجاه نحو تناقص معدلات الهطل لفصل الشتاء في محطة اللاذقية، والربيع في جميع المحطات. في حين لوحظ اتجاه نحو تزايد معدلات الهطل لفصل الشتاء في محطتي طرطوس وصافيتا، والخريف في جميع المحطات. على الرغم من أن جميع هذه الاتجاهات الخطية السالبة والموجبة على كلا المستويين السنوي والفصلي ليست معنوية إحصائياً عند مستوى 5%، إلا أنه يمكن أن يكون لها تأثيرات حادة على موارد المياه، ونظم جريان الأنهار ونجاح المحاصيل البعلية في مناطق الدراسة. In this study, trends of annual and seasonal precipitation time series for the period of (1971–2006) were analysed for three meteorological stations (Lattakia, Tartous and Safita) located in the coastal region of Syria, by linear regression and Spearman's rho tests. The results showed a decreasing trend of annual precipitation in Lattakia and Tartous stations and increasing trend in Safita station. At the seasonal time scale, a decreasing trends of winter precipitation in Lattakia station and of spring precipitation in all stations were observed. While an increasing trends of winter precipitation in Tartous and Safita stations and of autumn precipitation in all stations were observed. Although, all of these negative and positive linear trends, both at the annual and seasonal time scales are not statistically significant at 5% level, but they can have severe effects on water resources, rivers regimes and success of rain-fed crops in the study areas.